MRI TECHNIQUE OF DYNAMIC CONTRAST ENHANCEMENT APPLIED TO THE DIAGNOSIS AND MONITORING OF CHEMO-RADIATION TREATMENT OF SECONDARY BONE LESIONS - N. I. Sergeev (Сибирский онкологический журнал)
The data of 50 patients treated with chemo-radiotherapy treatment for metastatic lesions of the axial skeleton. The proposed technique MRI ADC «dual construct» can more accurately assess the early results of treatment.